Biodiversity Flora and Fauna in the Region Forest Bukit Datuk Dumai Riau Province - Heriyanto, Nur M.; Samsoedin, Ismayadi; Bismark, M. (Department of Forestry, Faculty of Agriculture, University of Lampung, 2019)
Research on the biodiversity of flora and fauna in conservation forests in the petroleum/oil refinery industri is rarely done, this activity aims to obtain information on the biodiversity of flora and fauna, especially bird species. This research was conducted in in the Bukit Datuk Dumai forest area, Riau Province. Ploting a plot of 100 m x 100 m (1 ha) is made for flora biodiversity, for bird plots with a radius of 25 m scattered randomly at that location. The structure and composition of tree species with a diameter at breast height 10 cm, saplings and seedlings were examined from a permanent measuring plot of one ha. There were 32 species of trees with a diameter of 10 cm and numbering 354 trees, belonging to 22 family, the largest species being Dipterocarpaceae. Species that dominate tree level stands are Garcinia dioca L. IVI = 39.67%, Gironniera subaequalis Planch. IVI = 30.39% and Ochanostachys amentaceae Mast. IVI = 30.26 %. The species in sapling level are Hopea mengarawan Miq., Gironniera subaequalis Planch. and Shorea acuminata Dyer. With IVI respectively 73.71%, 42.51% and 35.24%, seedlings of species Glochidion sp. With IVI 47.10%, Koompassia excelsa Taub. IVI 43.52% and Hopea mengarawan Miq. IVI24.62%. The number of bird species was found 33 with a diversity index of 2.63, an evenness index of 0.75 and a species richness index of 6.52.Keywords: structure, composition, regeneration, swamp forests, fauna, birds.